## Abstract

The enhancement of a dissolved chemical's Raman scattering by a liquid-core optical fiber (LCOF) geometry is absorption dependent. This dependence leads to a disruption of the usual linear correlation between chemical concentration and Raman peak area. To recover the linearity, we augmented a standard LCOF Raman spectroscopy system with spectrophotometric capabilities, permitting sequential measurements of Raman and absorption spectra within the LCOF.
Measurements of samples with identical Raman-scatterer concentrations but different absorption coefficients are described. Using the absorption values,
we reduced variations in the measured Raman intensities from
$60\%$ to less than
$1\%$. This correction method should be important for LCOF-based Raman spectroscopy of sample sets with variable absorption coefficients, such as urine and blood serum from multiple patients.

© 2006 Optical Society of America

Full Article |

PDF Article
### Equations (5)

Equations on this page are rendered with MathJax. Learn more.

(1)
$${P}_{R}\left(\tilde{\nu}\right)\approx c\text{\hspace{0.17em}}\frac{1-\mathrm{exp}\left[-\left({\mu}_{aL}+{\mu}_{aR}+2{\mu}_{s}\right)L\right]}{{\mu}_{aL}+{\mu}_{aR}+2{\mu}_{s}}\text{\hspace{0.17em}}\frac{AP\sigma}{{m}_{0}},$$
(2)
$${P}_{\mathrm{corr}}\left(\tilde{\nu}\right)={P}_{R}\left(\tilde{\nu}\right)\left\{\frac{{\mu}_{aL}+{\mu}_{aR}+2{\mu}_{s}}{1-\mathrm{exp}[-\left({\mu}_{aL}+{\mu}_{aR}+2{\mu}_{s}\right)L]}\right\}=c\text{\hspace{0.17em}}\frac{AP\sigma}{{m}_{0}}.$$
(3)
$${P}_{\text{sample}}\left(\lambda \right)={P}_{0}\left(\lambda \right)C\text{\hspace{0.17em}}\mathrm{exp}\left[-{\mu}_{a}\left(\lambda \right)L\right]={P}_{0}\left(\lambda \right)C\mathrm{exp}\left\{-\left[{\mu}_{a\text{,}W}\left(\lambda \right)+{\mu}_{a\text{,}C}\left(\lambda \right)\right]L\right\},$$
(4)
$${\mu}_{a}\left(\lambda \right)={\mu}_{a\text{,}W}\left(\lambda \right)+\frac{1}{L}\text{\hspace{0.17em}}\mathrm{ln}\left[\frac{{P}_{\text{water}}\left(\lambda \right)}{{P}_{\text{sample}}\left(\lambda \right)}\right].$$
(5)
$$\frac{P\left(z\right)}{P\left(z=0\right)}=\mathrm{exp}\left(-{\mu}_{a}z\right)\text{\hspace{0.17em}}\frac{2}{{\left(\gamma z\right)}^{2}}\text{\hspace{0.17em}}\mathrm{exp}\left(\gamma z\right)\left[\left(\gamma z-1\right)+1\right],$$